Efecto de los extractos de clinopodium taxifolium “chinininga” frente a las cepas de escherichia coli y salmonella typhimuriun in vitro.” - Quiroz Valiente, Eder Joel (2011)
Through this work entitled “Effect of Extracts from the leaves of Clinopodium taxifolium” “Chinininga” against strains of Escherichia Coli y Salmonella Typhimurium in vitro was performed in order to determine their antibacterial effects on strains of Escherichia Coli y Salmonella Typhimurium to verify the traditional use of the plant against acute gastrointestinal disease. To obtain the extracts were used extracts using solvents of increasing polarity: hexane, ethanol and aqueous extracts of wich were used to determine its effect on Escherichia Coli y Salmonella Typhimurium. According to Bauer kirbi diffusion method modified by diffusion of a sample through a layer of agar solidified, to an extent, the growth of sensitive organisms is inhibited around the area containing a known concentration of the hexane extract, ethanolic and aqueous Clinopodium taxifolium the “chinininga”. Corresponding test yielded the following results: For the hexane obtained higher inhibition zone of 12mm to 18mm for both microorganisms, for the ethanol extract was obtained halos of inhibition of 10mm to 12mm and for the aqueous extract of 9mm to 11mm. the results obtained showed that: the hexane extract showed higher inhibition halo of the extract, and the size of 12mm to 18mm and 10mm to 12mm for Escherichia Coli y Salmonella Typhimurium respectively, in addition to more concentration of then extracts and the antibacterial effect will be greater Escherichia Coli being the most sensitive